Production of sugars from lignocellulosic biomass via biochemical and thermochemical routes - Brown, Jessica; Lindstrom, Jake K.; Ghosh, Arpa; Rollag, Sean A.; Brown, Robert C. (Frontiers in Energy Research, 2024)
Sugars are the precursor to the majority of the world's biofuels. Most of these come from sugar and starch crops, such as sugarcane and corn grain. Lignocellulosic sugars, although more challenging to extract from biomass, represent a large, untapped, opportunity. In response to increasing attention to renewable energy, fuels, and chemicals, we review and compare two strategies for extracting sugars from lignocellulosic biomass: biochemical and thermochemical processing. Biochemical processing based on enzymatic hydrolysis has high sugar yield but is relatively slow. Thermochemical processing, which includes fast pyrolysis and solvent liquefaction, offers increased throughput and operability at the expense of lower sugar yields.